Effects of coenzyme q10 on lipid profile in streptozotocin induced diabetic rats - Deniz Uluışık; Ercan Keskin; Yasemin Öznurlu; Tuğba Özaydın (Eurasian Journal of Veterinary Sciences)
Aim: This research was carried out to evaluate the effects on lipid profile of Coenzyme Q10 in streptozotocin induced diabetic rats. Materials and Methods: In the study, 38 adult male Wistar Abino rats were divided into five groups. Group I animals was no applied. Group II animals was intraperitoneally administered 0.3 ml corn oil daily and group III animals was intraperitoneally administered 10 mg/kg CoQ10 in 0.3 ml corn oil daily for four weeks. In group IV animals, diabetes was induced by subcutaneous injections of 40 mg/kg streptozotocin for two days as a single dose per day. In group V animals, diabetes was induced by same protocol applied to group IV and then these animals were intraperitoneally administered 10 mg/kg CoQ10 in 0.3 ml corn oil for four weeks. It was determined plasma triglyceride, total cholesterol, LDL, HDL, insulin and glucose levels in all groups. In liver sections, the staining intensity of hepatocytes containing lipid droplets were evaluated. Results: Experimentally diabetes increased triglyceride, cholesterol and LDL levels, while these parameters decreased with CoQ10 treatment to diabetic rats when compared to diabetic group (P<0.05). Plasma HDL level was lower in diabetic group and plasma HDL level with CoQ10 treatment to diabetic rats increased to diabetic group (P<0.05). It was observed an increase in the staining intensity of hepatocytes containing lipid droplets in diabetes group. However, these staining intensity decreased by administration of CoQ10 to diabetic rats. Conclusion: According to these results, it could be say that CoQ10 treatment recovered lipid abnormalities of diabetic rats.